1988
DOI: 10.1002/eji.1830180712
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of lymphokine activities and helper function for IgE in human T cell clones

Abstract: A large panel of phytohemagglutinin (PHA)-induced T cell clones (690 in total), established from four different human lymphoid tissues (peripheral blood, tonsils, lymph nodes and spleens) by a high-efficiency cloning technique, was characterized according to their pattern of lymphokine production. The majority of both CD4+ and CD8+ clones from all lymphoid tissues produced interleukin (IL) 2 and/or interferon (IFN)-gamma in response to 24-h stimulation with PHA. In contrast, higher proportions of IL 4-producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(60 citation statements)
references
References 12 publications
2
58
0
Order By: Relevance
“…Alhydrogel did not stimulate either ovine IgGl or lgG2 preferentially. This lack of correlation between the sytithesis of particular lymphokines and Ig isotypes in sheep accorded with results from human T cell clones and lymphocyte cultures (22). The results differed from comparable studies in mice where the production of y-IFN by a subpopulation of helper T lymphocytes (f HI) increased lgG2p and depressed IgGl and IgE production (7.8.23).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Alhydrogel did not stimulate either ovine IgGl or lgG2 preferentially. This lack of correlation between the sytithesis of particular lymphokines and Ig isotypes in sheep accorded with results from human T cell clones and lymphocyte cultures (22). The results differed from comparable studies in mice where the production of y-IFN by a subpopulation of helper T lymphocytes (f HI) increased lgG2p and depressed IgGl and IgE production (7.8.23).…”
Section: Discussionmentioning
confidence: 58%
“…The data support the notion of an intrinsic immunomodulatory or mitogenic activity of individual adjuvants. While y-IFN has been reported as released from both helper and cytotoxie T lymphocytes (22), the source of y-IFN released within 24 h of inoculation of adjuvants into unprimed sheep was not clear. The results also indicated that the majority of y-IFN produced in response to adjuvanted ovalbumin was invoked by the particular adjuvant and not the antigen in the mixture.…”
Section: Discussionmentioning
confidence: 99%
“…Th1 cells produce IL-2 and IFN-but no IL-4 and IL-5, whereas Th2 cells were reported to produce IL-4 and IL-5 but no IFN-and IL-2. Th0 cells were identified as a common precursor of Th1 and Th2 cells which appear to produce IL-4 and IFN-, but only rarely IL-5 [18]. Thus, the production of IL-5 and IL-4 has been thought to be coregulated and produced by the same type of cell.…”
Section: Discussionmentioning
confidence: 99%
“…However, it also diverted attention from the functional plasticity of T cells. Even at that time, demonstrations of the co-expression of interferon-γ (IFNγ) and interleukin-4 (IL-4) from human T cell clones was prevalent 199,200 , and single cell analysis showed co-expression of T H 1-and T H 2-type cytokines, especially early after the initial stimulation of naive T cells 201 . Nevertheless, the capacity of CD4 + T cells to exhibit stably polarized phenotypes both in vitro (under specific polarizing conditions) and in vivo (in individuals with immunopathologies) supported the hypothesis that distinct T cell lineages can develop that supersede plasticity 2,3,201 .…”
mentioning
confidence: 99%